Dural arteriovenous fistula - Irina Dobrin (Romanian Neurosurgery, 2012)
Dural arteriovenous fistula (DAVF) are abnormal shunts between dural arteries and veins or venous sinuses of the dura mater. Also the connections may be between pachymeningeal arteries from cortical arteries and veins or sinus from dura mater. There are uncommon pathologic entities, 6-8 % from supratentorial vascular malformations, and about 20-30% of infratentorial vascular pathology (8). The incidence may be higher because only 10% are symptomatic. The clinical manifestations are very variable from simple cephalea to major intracranial hemorrhagic ictus. The presentation is usually in the adult period,but are citied cases in childhood. In our country the diagnostic was difficult before the digital substraction angiography ( DSA) and the endovascular treatment was started in 2004 in our Department under coordination of professor Patrick Courtheoux from Caen, France.